Lean Muscle Mass in Classic or Ovulatory PCOS: Association with Central Obesity and Insulin Resistance - Mario, F. M.; do Amarante, F.; Toscani, M. K.; Spritzer, P. M. (Experimental and Clinical Endocrinology & Diabetes, 2012)
This age-matched case-control study assessed total and segmental lean muscle mass in classic or ovulatory polycystic ovary syndrome (PCOS) patients and investigated whether lean mass is associated with hormone and metabolic features. Participants underwent anthropometric and clinical evaluation. Habitual physical activity was assessed with a digital pedometer, and body composition by dual-energy X-ray absorptiometry. Laboratory measurements included total cholesterol, cholesterol fractions, triglycerides, glucose, total serum testosterone, serum insulin, estradiol, luteinizing hormone, and SHBG. Energy intake was calculated using a food frequency questionnaire. Classic PCOS patients had higher body mass index (BMI), waist circumference, testosterone and lipid accumulation product values than ovulatory PCOS and controls. Energy consumption, homeostasis model assessment index, SHBG, free androgen index and triglycerides, total and trunk lean mass were higher only in classic PCOS women vs. controls. Arm, leg, trunk, total or limb lean masses were not correlated with hormone levels in any of the groups. However, in PCOS women lipid accumulation product was positively correlated with total (r=0.56, p=0.001), trunk (r=0.59, p=0.001), arm (r=0.54, p=0.001), leg (r=0.44, p=0.03) and limb (r=0.48, p=0.001) lean masses. BMI was positively correlated with all lean mass segments and independently associated with total lean mass. Lipid accumulation product and BMI were independently associated with trunk lean mass variation. The increase in lean mass in classic PCOS appears to be associated with insulin resistance and central obesity rather than with energy intake, physical activity or androgens.
Keywords: hyperandrogenemia; polycystic ovary syndrome; metabolic features; obesity